IMPLEMENTING MEDIA LITERACY INTO THE EDUCATION CURRICULUM OF PRESERVICE PRIMARY SCHOOL TEACHERS - Ishutina, Olena (Професіоналізм педагога: теоретичні й методичні аспекти, 2020)
The article analyses the state of the system of media education in the context of professional training preservice primary school teachers. It is proved that integration of media literacy into educational curriculum of the students is a relevant issue not only for higher education in Ukraine but in other countries as well. The article provides an analysis of Concept of Media Education Implementation in Ukraine (2010) that reveal the process of organizing media studies in our country. Analysis of current research conducted by scientists has shown that media education should be based on the study of six key concepts: media agencies, media categories, media technology, media languages, media audience, and media representation. At the same time, the analysis of the studies aimed at the level of organization of media education in Ukraine, developing teachers’ skills in media education, strengthening the media literacy of students, improving their critical thinking has revealed the state’s interest in forming and developing media competent educators and media literate citizens. The purpose of the article is to analyse the state of integration of media literacy of preservice primary school teachers into the system of professional education. After media education was declared a priority for the development of education in the 21st century by UNESCO, the issue of modernization of teacher training in higher education institutions has become crucial. The article provides an analysis of Concept of Media Education Implementation in Ukraine (2010) that reveal the process of organizing media education in Ukraine. The analysis of modern research conducted by scientists has shown that media education in professional training includes targets for the development of preservice primary school teachers, the development of a holistic perception and analysis of media texts, individual creative and critical thinking. The components of media education for teachers include 4 types of training, which are closely related: methodological (knowledge in the field of aesthetics, philosophy, pedagogy and psychology; knowledge of a man as a spiritual being, personality and individuality; knowledge of historical ways of formation of mass media); theoretical (knowledge of the theory of mass media, their functions in modern society, methods of possible manipulation of mass consciousness, methods of analysis of mass media messages); methodical (mastering knowledge about the content, forms, methods and means of media education); practical (preservice primary school teachers’ training for media education, developing skills and abilities in the field of media education, as well as skills and abilities of a special nature that allow to solve specific educational and practical problems). The study and analysis of Ukrainian and world experience shows the existence of three areas of integration of media education elements in the educational process at university: introduction of a subject as an invariant part of the curriculum (the so-called special media education); solving the problems of media education due to the variable part (optional media education); solving the problems of media education in general while studying special courses on teaching methods at primary school (integrated media education).